A two-stage multi-attribute analysis method for city-integrated hybrid mini-grid design. (February 2021) - Elkadeem, M.R.; Kotb, Kotb M.; Ullah, Zia; Atiya, Eman G.; Dán, András; Wang, Shaorong
Highlights: A two-stage multi-attribute analysis method for optimal design of sustainable energy system is proposed. Different alternatives are optimized based on energy, environmental, economic, and social attributes. Effect of uncertainty parameters on the designed system structure and cost is examined. PV-WT-BAT-CONV mini-grid is the most sustainable alternative in El-Qsier urban city, Egypt. Load growth and battery cost have high impacts on investment decision rather than RE resources. Abstract: This paper proposes a two-stage multi-attribute analysis method in conceptualizing the feasible electrification strategy with optimal capacities for a mid-rise building situated in El-Qsier urban city, Egypt. The proposed model measures the implementation practicability of hybrid mini-grid against stand-alone diesel and the utility grid extension systems. The model takes into consideration, simultaneously, a total of 12 attributes covering technical, economic, environmental, and socio-political sustainability aspects. First, an accurate Energy-Enviro-Economic (3E) optimization analysis is performed to determine the set of feasible configurations using HOMER Pro software. Second, a Multi-Attribute Decision Making (MADM) model is established based on AHP, TOPSIS, VIKOR, CODAS, WASPAS methods to identify the unique best alternative. The results of the 3E optimization and decision making analyses confirm the non-viability of the reference site for grid extension against other off-grid systems. Also, the 100 % hybrid renewable mini-grid system is nominated as the most sustainable design, and it yielded optimal capacities of 196 kW, 72 kW, 587 kW h, and 75 kW for photovoltaic, wind turbine, converter, and battery. The system has total life-cycle and energy costs of 751, 597 and 0.2374/kWh, respectively, with a zero-emission value and maximum social benefits equals 0.6089 jobs/year. Meanwhile, the sensitivity analysis elucidates that the load growth and battery cost have a high impact on investment decisions rather than solar irradiance and wind speed.